Reinterpreting the Geneva Conventions: The Bush Administration and the Legal Framework on Torture - Konings, Iza (Colloquium: The Political Science Journal of Boston College, 2025)
The rules and regulations established in the Geneva Conventions serve, in theory, to protect basic human rights during times of war, and are used to punish those found in violation. The Conventions regulate "the conduct of armed conflict and seek to limit its effects" while "specifically protect(ing} people who are not taking part in the hostilities ... and those who are no longer participating such as wounded ... and prisoners of war." However, in the wake of the September 11, 2001 terrorist attacks on the United States, the Bush administration sought to reinterpret the Conventions and initiated huge shifts in the way international humanitarian law 1vas-or was not-applied to specific circumstances. These shifts radically undermined the protections enshrined in international law and allowed the U.S. government to bypass due process when dealing with the people who were caught in the military apparatus of the post-9/11 wars. This reshaping of American legal norms was not merely a response to the changing nature of warfare; instead, it constituted a calculated and deliberate project to extend executive authority and allow for the legal protection of those in the U.S. government who committed breaches of international humanitarian law. In this paper, I will argue that the Bush administration's reinterpretation of the Geneva Conventions reflected a strategic departure from traditional international norms and laws, as it sought to redefine the legal status of detainees in the War on Terror in order to expand executive power and justify enhanced interrogation tactics. This resulted in the establishment of legal gray zones in which prisoners were deprived of their fundamental human rights, and the framework surrounding lawful conduct in armed conflict was severely eroded, thereby setting deeply troubling precedents for future wars.